Why Masters are Necessary. Upstream Considerations Starting from a María Zambrano's Book - Massimo Pomi (University of Bologna, 2018)
Why to read it again, today, the even brilliant pages on the role of master from the Spanish philosopher María Zambrano? Her undated reflections recall us to the persistent actuality of a crucial issue: how to give continuity to the western rationality in its philosophical and intellectual thickness over the time. In front of solutions devoid of historical memory to the huge problems related to the mass education, in view of the cultural and civil formation of the new generations, from these notes it is possible to articulate the essential issues of a topic that track down in master's Idealtypus the indispensable player to attempt to convert loneliness, confusion, hopelessness and the stubborn silence of too many pupils into a brave search for sense. This moves from the questions posed by everyone and open to the obstinate "courage to exist", indispensable for dealing with the future.